1998
DOI: 10.1001/archderm.134.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis Due to Leishmania infantum

Abstract: Background: Leishmania infantum recently has been identified as a possible agent of cutaneous leishmaniasis (CL). This species has been isolated from cutaneous lesions of patients from the Mediterranean Basin. However, little is known about the clinical, biological, or therapeutic features of this newly recognized CL.Observations: Six patients aged 9 months to 85 years in southeastern France were found to have autochthonous leishmaniasis. Parasitological identification showed that the agent was L infantum, zym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 39 publications
5
72
0
9
Order By: Relevance
“…L. infantum is well recognized as the etiological agent of VL in southern Europe and is much less commonly reported as a cause of CL [2]. Mucosal forms of L. infantum infection are very rare [35].…”
Section: Introductionmentioning
confidence: 99%
“…L. infantum is well recognized as the etiological agent of VL in southern Europe and is much less commonly reported as a cause of CL [2]. Mucosal forms of L. infantum infection are very rare [35].…”
Section: Introductionmentioning
confidence: 99%
“…Endemic areas in France are the regions of Languedoc-Roussillon and Provence-Alpes-Côtes d’Azur [1,2,3]. L. infantum (most frequently zymodeme MON-1 ) is a species responsible for VL, mainly in children or immunocompromised hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, L. infantum (also zymodeme MON-1) can cause localized CL in immunocompetent hosts. In France, autochthonous CL has a very low incidence (estimated as 0.5 per million a year) and VL remains rare [1,2,3]. However, studies based on leishmanin skin testing or serological tests have shown a high seroprevalence for leishmaniasis (from 10 to 60% of healthy carriers depending on age and county) [1,2,3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Journal of Infection (2005) Based on the relative tropism of Leishmania and the immune status of the host, Leishmaniases are classified into cutaneous, mucocutaneous and visceral. The cutaneous forms are generally divided into Old World CL, related to Leishmania of the major and donovani complexes, and New World CL, caused by the L. mexicana and L. braziliensis complexes.…”
Section: Introductionmentioning
confidence: 99%